Raman micro spectroscopy for in vitro drug screening: subcellular localisation and interactions of doxorubicin. Issue 12 (21st June 2015) - Farhane, Z.; Bonnier, F.; Casey, A.; Byrne, H. J.
<x xml:space="preserve">Abstract</x> Raman spectroscopy is used for the localization and tracking of chemotherapeutic drug, doxorubicin, in the intracellular environment of lung cancer cell line. Results show the potential of the technique to monitor the mechanisms of action and response on a molecular level, with subcellular resolution.